(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the conditions of Uzbekistan, it consists in studying the bioecological characteristics of maple (Acer platanoides), Semenov maple (Acer semenovii) and Pennsylvanian ash (Fraxinus pennsylvanica Marsh.), developing the breeding technology for Acer platanoides), Semenov maple (Acer semenovii). ) and Pennsylvanian shumtoli (Fraxinus pennsylvanica Marsh.), bioecological features are being studied, and breeding technologies are being developed.